Web-Based Ranking and Link Analysis of NAAC Accredited General Degree Colleges in West Bengal: A Webometric Study - Ghosh, Sanjib; Roy, Bijan Kumar (Journal of Information and Knowledge, 2022)
This study examines the websites of 36 NAAC-accredited general degree colleges in West Bengal using Webometric indicators. Webometric data is acquired on the Google search engine using special query syntax and calculated different WIFs and WISER value of websites, the relationship between the ranks of all websites as defined by WISER indexing value and in-link impact value are also examined. According to the findings, Panihati Mahavidyalaya's website under West Bengal State University ranked first in Simple Web Impact Factor (SWIF) with 1887.912%, and Banipur Mahila Mahavidyalaya's websites (Sl. No. 5) ranked first in self-link WIF, INLWIF, and EWIF with 0.679803 SLWIF, 0.729064 ELWIFs, and 0.315271 RWIFs, respectively. Darjeeling Govt. College is ranked first, followed by Panihati Mahavidyalaya and Mugberia Gangadhar Mahavidyalaya, according to the WISER index value. This study may aid college administrators and webmasters in better comprehending the importance of these websites in making them user-friendly and informative websites that meet the needs of their users.